Studi Pendahuluan Rantai Pasok Kopi Di Bogor : Studi Kasus Pada Perkebunan Kopi Bunga - Hadi, Cecilia Valentina Sri; Sekar, Safina (Jurnal Aplikasi Bisnis Kesatuan, 2024)
The importance of knowing the certainty of coffee supply for consumers is as important as knowing how coffee plants are cared for in a coffee plantation and then the coffee plants are fertile and finally able to produce good coffee beans and in relatively adequate quantities to be able to meet the supply from upstream to downstream. The research method uses qualitative descriptive with key informants being stakeholders in the coffee bean supply chain from upstream to downstream. SWOT (Strengths, Weakness, Opportunity, Thread) analysis is used to obtain the status of potential sustainability of supply to stakeholders in the coffee supply chain from coffee plantation flowers.   Keywords: coffee plantation; coffee supply chain, coffee farmers, coffee